Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.36108/njsa/7002/50(0160)
|View full text |Cite
|
Sign up to set email alerts
|

The Challenges of National Integration in Nigeria

Abstract: This paper interrogates the challenges of national integration in Nigeria. Several policies and programmes of government like harmonized state structure, establishment of National Youths Service Corps Scheme, Federal Character Commission have not been able to achieve the goal of unifying the peoples of Nigeria. The question is, what are the factors responsible for lack of unity, tribalism, nepotism, electoral malpractices, anarchy and social disorganisation, which are the bane of the Nigerian soda-political st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This includes even small parts east of southern Africa. This is positive news in view of the importance and extensive use of cassava as a food security crop and for biofuel production ( Nweke, 2004 ). This observation is consistent with other studies, which reported that suitable habitats for Cassava would increase across Africa ( Jarvis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…This includes even small parts east of southern Africa. This is positive news in view of the importance and extensive use of cassava as a food security crop and for biofuel production ( Nweke, 2004 ). This observation is consistent with other studies, which reported that suitable habitats for Cassava would increase across Africa ( Jarvis et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, this perspective has been challenged for neglecting the presence and contributions of citizens and other non-state actors to national security. The second perspective argues that defence is different from security because security is all-encompassing and usually includes the well-being of the citizens of a country and not just the protection of national boundaries and authoritarian regimes from threats (Nnoli, 2006;Nweke, 1988). The third perspective argues that anything can be securitised and made to look like a threat to the existence and survival of a state (Buzan et al, 1998).…”
Section: Migration Securitisation and National Securitymentioning
confidence: 99%
“…Imobighe (1981) refers to it as the defense and survival of the state. The danger of looking at national security from this narrow angle according to Nweke (1988) is three-fold; but we shall concern ourselves with the first two: First is the tendency to equate "defense" with "security" and to bestow undue responsibilities to the military as if the armed forces alone are the guardians of national security. This tendency in turn creates in the minds of the armed forces that it is only through them that security, stability and progress can be achieved.…”
Section: National Securitymentioning
confidence: 99%